The Effect of Organizational Structure on Organizational Commitment in Tishreen University (Journal of Hama University, 2022)
The research aimed to study the Effect of Organizational Structure on Organizational Commitment in Tishreen University; the researcher collected the data through a questionnaire is prepared based on previous studies, and applied the class random sampling during the distribution of the questionnaire to the research community, which includes academics and administrative staff.The results of the research showed there is medium level of Organizational Commitment in Tishreen University, also high level of complexity and medium level of centralization and formalization. In addition, it showed there is a very weak significant effect of centralization and complexity onOrganizational commitment, also there is a very weak significant effect of organizational structure on organizational commitment.
Keywords: Organizational Structure; Centralization; Formalization; Complexity; Organizational Commitment